2020
DOI: 10.1111/iji.12463
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in IL‐1A are associated with endometrial cancer susceptibility among Chinese Han population: A case–control study

Abstract: Endometrial cancer (EC) is one of the most common malignant tumours of the female genital tract, and it has become a serious malignant disease of the female genital tract in China. Existing researches have revealed the association between polymorphisms of IL‐1A and several gynaecological diseases. In this research, we analysed the association between IL‐1A gene polymorphisms and endometrial cancer susceptibility in Chinese female population. A total of 81 patients and 198 healthy people were selected. Odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Until now, very few articles have been published on the association between serum levels and gene polymorphisms of IL‐27 and the risk of endometriosis. However, in ovarian or endometrial cancers that share similar molecular pathogenesis with endometriosis (Kori et al., 2016; Liu et al., 2020), some studies indicated that IL‐27 protein or IL27‐p28 transcript declined (Zhang et al., 2014; Zhao et al., 2020). Besides, the G allele of IL‐27 rs153109 was higher in patients with ovarian cancer or endometrial cancer (Liu et al., 2016; Zhang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, very few articles have been published on the association between serum levels and gene polymorphisms of IL‐27 and the risk of endometriosis. However, in ovarian or endometrial cancers that share similar molecular pathogenesis with endometriosis (Kori et al., 2016; Liu et al., 2020), some studies indicated that IL‐27 protein or IL27‐p28 transcript declined (Zhang et al., 2014; Zhao et al., 2020). Besides, the G allele of IL‐27 rs153109 was higher in patients with ovarian cancer or endometrial cancer (Liu et al., 2016; Zhang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The single nucleotide polymorphism (SNP) is the most common form of human genetic variations, which are significantly linked to the risk of tumorigenesis. It was reported that the polymorphisms in rs3783553, rs3783550, rs3783546, rs1609682 and rs3783521 of IL-1α ( 138 , 139 ), rs1524107 and rs2066992 of IL-6 ( 140 ), rs4758680 and rs7977932 of IL-31 ( 141 ), rs28372698 and rs12934561 of IL-32 ( 2 ) may be relevant to increased susceptibility to EC in Chinese women. Moreover, the CC genotype of IL-6 Gene (−174 & -572) might contribute to EC risk ( 142 ).…”
Section: Clinical Application Of Interleukins In Ecmentioning
confidence: 99%
“…According to the latest cancer statistics reported in the United States in 2020, EC has ranked the fourth of newly diagnosed cases of female malignant tumor ( 2 ). In many economically developed areas of China, EC has become the most common malignant tumor of female reproductive system, and the incidence is increasing year by year, such as Beijing, Shanghai, and Guangzhou ( 3 ). Studies have reported that most patients with EC are diagnosed at the early stage (80% of stage I patients), and the 5-year survival rate could reach 95%.…”
Section: Introductionmentioning
confidence: 99%